Drawing on difference : art therapy with people who have learning difficulties - Rees, Mair, 1960- (London ; New York : Routledge, 1998)
Drawing on Difference reveals how art therapy can support and validate the emotional and mental health needs of people with learning difficulties. Case studies present work with adults and children with differing degrees of difficulty.
Personal journey / Richard Manners -- Frames of reference : some operational and contextual issues influencing the practice of art therapy with people who have learning difficulties / Mair Rees -- It's a mystery : accounts of an art therapy group for people with learning difficulties / Hilary Lomas and Penny Hallas -- On the edge : art therapy for people with learning difficulties and disordered personalities / Simon Willoughby-Booth and Joanna Pearce -- Lost in space : the relevance of art therapy with clients who have autism or autistic features / Lesley Fox -- Humpty Dumpty's shell : working with autistic defence mechanisms in art therapy / Margaret Stack -- Rape! : The violation of integrity and will / Rose Hughes -- Is art therapy? : Some issues arising in working with children with severe learning difficulties / Sigrid Räbiger -- Learning to say 'goodbye' : loss and bereavement in learning difficulties and the role of art therapy / Ed Kuczaj -- Journey in joint working : some reflections on an experience of arts therapies collaboration / Chris Gale and Rachel Matthews -- Chances for change : counselling people with learning difficulties / Lillie Fennell and Enfys Jones -- There is a light at the end of the tunnel : ways to good 'clinical effectiveness research' / Sandie Taylor -- Clinical supervision in art therapy : is it really 'super!'? / Mair Rees.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: People with mental disabilities -- Rehabilitation; Art therapy; People with mental disabilities -- Mental health; Art Therapy; Persons with Intellectual Disabilities -- rehabilitation; Personnes ayant une déficience intellectuelle -- Réadaptation.; Art-thérapie.; Personnes ayant une déficience intellectuelle -- Santé mentale; art therapy; PSYCHOLOGY -- Neuropsychology; Art therapy; People with mental disabilities -- Mental health; People with mental disabilities -- Rehabilitation; Kunsttherapie; Lernstörung; Aufsatzsammlung